Ethics of Biotechnology in Bioshock’s Interactive Narrative - Oktodila, Hasbi Thaufik; Hapsarani, Dhita (KnE Social Sciences, 2019)
The interactivity element in video games allows the process of delivering narration through words and actions taken by the game player. The diversity of game design in delivering stories leads to a debate between ludology (game-centered) and narratology (narrative-centered). Ludology perceives game as ‘sets of rules’ because game itself is a medium that is made up of rules. On the other hand, narratology views game in terms of the narrative resulted from the rules. Narratology tends to reduce the peculiarity of the medium because it does not take game rules into account, while ludology ignores the narrative elements. However, in recent times, games combine aspects of gameplay and narration to form an interactive narrative. One video game that uses such combination is Bioshock (2007). The interactivity elements in this game are not only for conveying the story, but also for allowing players’ participation to determine the resolution of the story through the player’s interaction with the character named Little Sister. Gameplay-wise, Little Sister acts as one of the main resources that helps players complete the game. Narrative-wise, Little Sister who is a chimera (a combination between animal and human) is a representation of technological advancement. Positioned as resource both in the gameplay and the narration, the game player’s treatment toward Little Sister implies ethical and moral consequences. For these reasons, this article implements textual analysis to discuss the characterization of Little Sisters displayed in the gameplay and the narration that leads to the ethical and morality issues lies in biotechnology. Keywords: Biotechnology, chimera, interactivity, moral-ethics, video game criticism.